2021
DOI: 10.1298/ptr.e10081
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Patients Showed Improvements in Balance in Response to Visual Restriction Exercise

Abstract: Objective: Several strategies have been designed to improve balance after stroke. Although recent studies have suggested that the balance training in stroke should include exercises that are performed in different sensory conflict conditions, little attention has been paid to manipulation of visual input. This study aimed to compare effects of balance training on an unstable surface with balance training under visual deprivation conditions in persons with stroke. Method: Forty-five stroke patients were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Similarly, there are studies in the literature showing that visual exercises also affect balance performance (Correia et al, 2021;Durall, 2012;Jandaghi et al, 2021). However, we think that more studies are needed to reveal the effects of these exercises on the balance of both female and male athletes.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, there are studies in the literature showing that visual exercises also affect balance performance (Correia et al, 2021;Durall, 2012;Jandaghi et al, 2021). However, we think that more studies are needed to reveal the effects of these exercises on the balance of both female and male athletes.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, the results obtained in this study indicate that the balancing exercise of sensory feedback to an extent at a range of non-perceptual levels could help improve walking ability by the participants' enhanced feedback to the somatosensory and vestibular systems. In a recent study, balance exercises under restricted visual conditions increased somatosensory and vestibular feedback and improved walking ability more than exercises on unstable surfaces [28]. When standing on an unstable surface, the central nervous system is more sensitive to sensory feedback from the visual and vestibular systems and less sensitive to feedback received from the somatosensory system.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, both studies demonstrate significant improvement in balance and ADLs. These findings may be explained by the fact that visual feedback therapies are proved to be effective in improving a symmetrical stance and in gaining a sitting balance [ 46 , 47 ]. Moreover, task specific activities given to both groups also promote cerebral activation and brain reorganization and bring maximum improvement in functional performance [ 27 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, both studies demonstrate significant improvement in balance and ADLs. These findings may be explained by the fact that visual feedback therapies are proved to be effective in improving a symmetrical stance and in gaining a sitting balance [46,47]. Moreover, task specific activities given to both groups also promote cerebral activation and brain reorganization and bring maximum improvement in functional performance [27 A retrospective study also reviewed the records of 220 patients suffering with either stroke or traumatic brain injury to investigate the frequency of eye movement dysfunctions and found that among 220 patients, cranial nerve palsy III and strabismus had the peak incidence rate [48].…”
Section: Gaze Palsies III Iv and Vimentioning
confidence: 99%